Assessment of Muscle Activation of Caregivers Performing Dependent Transfers With a Novel Robotic-Assisted Transfer Device Compared With the Hoyer Advance. (14th September 2021) - Blaauw, Eline R.; Greenhalgh, Mark; Vegter, Riemer; Bass, Sarah; Kulich, Hailee; Grindle, Garrett G.; Cooper, Rosemarie; Koontz, Alicia M.; Cooper, Rory A.
Abstract : Objective: The purpose of this study was to compare muscle activity in caregivers while using a novel robotic-assisted transfer device (Strong Arm) to a clinical standard of care (Hoyer Advance). Design: A quasi-experimental design was used in which 20 caregivers (33 ± 15 yrs old) performed transfers with three surfaces (toilet, bench, and shower chair) with the Strong Arm and Hoyer Advance. Transfer completion time (seconds), peak percentage surface electromyography (EMG), and integrated EMG of the bilateral erector spinae, latissimus dorsi, pectoralis major and anterior deltoid were measured. Results: Caregivers required less transfer time when transferring from wheelchair to surface using the Hoyer Advance ( P = 0.011, f = 0.39). For the lower back, significantly lower peak percentage EMGs were found using Strong Arm in 50% and for the integrated EMG in 25% of the cases, with the remaining cases showing no significant differences. For the shoulder, significantly lower peak percentage EMG values were found using Strong Arm in 19% of transfers and lower integrated EMG was found in 25% of transfers when using the Hoyer Advance, with the remaining cases showing no significant differences. Conclusion: Although back muscle activation during Strong Arm transfers is statistically, but not clinically, lower, additional features that couple with significantly lower muscle activation make it an alternative to the clinical standard for further research and possible clinical applicability.